THE DEVELOPMENT OF OBSERVATION STUDENT WORKSHEET IN ENGLISH VERSION OF INVERTEBRATES FOR GRADE X BASED ON SCIENTIFIC APPROACH - Ayu Kusumawardhani; Raharjo Raharjo (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2019)
Animalia Kingdom is one of biology topics in grade X  that use observation activity in its learning. Teaching materials that contain student activities by making observations are needed to create active and effective learning. This research aimed to produce Observation Student Worksheet in English Version Invertebrates Materials for Grade X Based on Scientific Approach as well as describe its validity, practicality, and effectivity. The development of student worksheet was conducted at Biology Department, The Faculty of Mathematics and Natural Science, Universitas Negeri Surabaya used 4D Model (Define, Design, Develop, Disseminate) and for the Disseminate stage not done. The trial was implemented in SMA Negeri 1 Bojonegoro using one group pretest and postest design.  The data of student worksheet validity, practicality, and effectivity was analyzed descriptive qualitatively. Based on validation result, student worksheet was valid (score 3.79). Based on learning effectiveness, student worksheet was practical (score 94.07%), students also give positive response to the worksheet (90.67%). The student worksheet was effective, based on the study result (80% of students can master the lesson). Based on the data obtained and analyzed, student worksheet was feasible to use in terms of validity, practicality, and effectiveness.   Key word: observation, student worksheet, scientific approach, invertebrates.